Blockout 2024: digital mobilization movements’ role in raising global awareness and fostering change - Sutikno, Tole; Handayani, Lina (International Journal of Informatics and Communication Technology (IJ-ICT), 2024)
Blockout 2024, a social media mobilization campaign, gained traction in response to celebrities’ and powerful people’s silence following the Met Gala in New York. Users who have remained silent or unconcerned about the humanitarian situation in Gaza are encouraged to block influencers’ accounts. The review seeks to investigate the Blockout 2024 phenomenon and how it affects celebrities’ social media. This review examines the impact of social media on power dynamics. On social media platforms such as TikTok, Instagram, and X, users have blocked the accounts (especially celebrities’ account) of those who have not responded to the humanitarian disaster. The movement emphasizes the importance of implementing change and making underrepresented voices heard in digital environments. While some celebrities have expressed their support, others have chosen to remain silent, which has resulted in criticism and lost followers. Finally, the Blockout 2024 campaign has gained significant traction on social media platforms such as X, Instagram, and TikTok. Users of social media are becoming more aware of their responsibility to denounce crimes and fight for justice, as evidenced by this group effort. The Blockout 2024 movement has highlighted the potential of digital mobilization to raise global awareness, address humanitarian crises, and hold influencers accountable.